2015
DOI: 10.1021/acs.langmuir.5b02545
|View full text |Cite
|
Sign up to set email alerts
|

Rationalization and Prediction of the Equivalent Alkane Carbon Number (EACN) of Polar Hydrocarbon Oils with COSMO-RS σ-Moments

Abstract: The equivalent alkane carbon numbers (EACNs) of 20 polar hydrocarbon oils are determined by the fishtail method. These values supplemented by 43 already reported EACNs of other hydrocarbons are rationalized by using the COSMO-RS σ-moments as descriptors for a QSPR analysis. A reliable model, with only two meaningful physicochemical parameters, namely the surface area (M0(X)) and the overall polarity (M2(X)) of the oil X, is able to predict the EACN values of a large variety of oils including (cyclo)alkanes, (c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 33 publications
1
15
0
Order By: Relevance
“…The results of research carried out in the first decade of the 21st century (Do et al, ) corroborated the polar oil EACN with different kinds of extended surfactants, for instance, of soya oil at EACN = 17.7 ± 0.5, in striking agreement with the originally reported value (Miñana‐Pérez et al, ) of EACN = 18 ± 1. This kind of result clearly indicates that an ester group decreases the EACN by about 10–12 units with respect to the total number of carbon atoms in a tail, a clear consequence of its polarity contribution to the oil (Engelskirchen et al, ; Lai et al, ; Lukowicz et al, , ; Ontiveros et al, ).…”
Section: Physicochemical Properties Of Extended Surfactantsmentioning
confidence: 97%
“…The results of research carried out in the first decade of the 21st century (Do et al, ) corroborated the polar oil EACN with different kinds of extended surfactants, for instance, of soya oil at EACN = 17.7 ± 0.5, in striking agreement with the originally reported value (Miñana‐Pérez et al, ) of EACN = 18 ± 1. This kind of result clearly indicates that an ester group decreases the EACN by about 10–12 units with respect to the total number of carbon atoms in a tail, a clear consequence of its polarity contribution to the oil (Engelskirchen et al, ; Lai et al, ; Lukowicz et al, , ; Ontiveros et al, ).…”
Section: Physicochemical Properties Of Extended Surfactantsmentioning
confidence: 97%
“…Decades of studies have reported more detailed effects and thus more precise variable contributions, including the non-alkane oil equivalent ACN effect (so-called EACN) [2,[12][13][14][15][16][17][18][19][20][21][22][23], and details on the alcohol co-surfactant effect f(A) [3-5, 24, 25] or the pressure effect [26][27][28][29][30], and even the influence of molecular variation in the surfactant structure characteristics such as the n-alkyl tail length, tail branching, ionic head group, polyethylene oxide or polypropylene oxide length [10,16,[31][32][33][34][35][36], or effect of a surfactant mixture composition [37,38]. There is no need to deal with all these details for the subject of this article, so only the variables indicated in Eq.…”
Section: Introductionmentioning
confidence: 99%
“…Bouton et al proposed a Quantitative Structure Property Relationship (QSPR) for the prediction of the EACN of hydrocarbons by means of two theoretical descriptors, i.e., the average negative softness and the Kier A3 [9], with EACN values in between À4 and +35. More recently, Lukowicz et al proposed a QSPR based on COSMO-RS r-moments to predict EACN of polar hydrocarbon oils [10] and then extended their model to the case of aprotic polar oils [11]. To determine EACN of hydrocarbon mixtures, Cayias et al [12] and Cash et al [13] proposed the use of a mixing rule in which individual hydrocarbon EACNs are weighted according to corresponding mole fractions.…”
Section: Introductionmentioning
confidence: 99%